The Entrepreneurship in Ecuador, Chile and Colombia. - Salazar Salazar, Fernando; Nayascual Ipial, Lady; Nayascual Ipial, Luis (SATHIRI, 2020)
This research has a quantitative approach, it also non-experimental, descriptive and correlational, wich considered the data of the Gem reports of Chile, Colombia and Ecuador of 2016 and 2017; for the purpose of determining whether the rates of nascent enterprises (TEN), early enterpreneurial activity (TEA) and closure of business (CN) have some relationship with the state of the enterpreneurship ecosystem. The main results suggest that financial support, government polices, government programs and the transfer of R&D; they are very sensitive can even explain, above 30%, the behavior in the rate of business closure.
Keywords: Ecuador; Colombia; Chile; Enterpreneurchip; Financing